Role of 3-Hydroxy Fatty Acid-Induced Hepatic Lipotoxicity in Acute Fatty Liver of Pregnancy - Sathish Kumar Natarajan; Jamal A. Ibdah (2018)
Acute fatty liver of pregnancy (AFLP), a catastrophic illness for both the mother and the unborn offspring, develops in the last trimester of pregnancy with significant maternal and perinatal mortality. AFLP is also recognized as an obstetric and medical emergency. Maternal AFLP is highly associated with a fetal homozygous mutation (1528G>C) in the gene that encodes for mitochondrial long-chain hydroxy acyl-CoA dehydrogenase (LCHAD). The mutation in LCHAD results in the accumulation of 3-hydroxy fatty acids, such as 3-hydroxy myristic acid, 3-hydroxy palmitic acid and 3-hydroxy dicarboxylic acid in the placenta, which are then shunted to the maternal circulation leading to the development of acute liver injury observed in patients with AFLP. In this review, we will discuss the mechanistic role of increased 3-hydroxy fatty acid in causing lipotoxicity to the liver and in inducing oxidative stress, mitochondrial dysfunction and hepatocyte lipoapoptosis. Further, we also review the role of 3-hydroxy fatty acids in causing placental damage, pancreatic islet β-cell glucolipotoxicity, brain damage, and retinal epithelial cells lipoapoptosis in patients with LCHAD deficiency.